2005
DOI: 10.1590/s0004-27302005000500022
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasias associadas à síndrome dos ovários policísticos

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disease in women on reproductive age. PCOS is characterized by the presence of anovulation, infertility and hyperandrogenism and is associated with obesity and insulin resistance. A major risk for neoplasms of the reproductive tract, like endometrial, breast and ovary cancer seems to be related to PCOS. While several studies have shown an increased risk for endometrial hyperplasia and cancer in PCOS patients, the variability of the selection criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
2
0
0
1
Order By: Relevance
“…a large cohort study also suggested increased risk of invasive and borderline ovarian tumours among women using clomiphene citrate for 12 months or longer (24). This finding was confirmed by other studies (25,29) In contrast, several other epidemiological studies failed to confirm the above findings and showed no association between women exposed to treatment with ovulation inducing drugs and untreated infertile women (14,15,16,24). some studies suggest that BRCA mutation carriers may have decreased ovarian reserve compared with women without BRCA mutations, as well as an earlier natural menopause (33).…”
Section: Aim Of the Studysupporting
confidence: 72%
“…a large cohort study also suggested increased risk of invasive and borderline ovarian tumours among women using clomiphene citrate for 12 months or longer (24). This finding was confirmed by other studies (25,29) In contrast, several other epidemiological studies failed to confirm the above findings and showed no association between women exposed to treatment with ovulation inducing drugs and untreated infertile women (14,15,16,24). some studies suggest that BRCA mutation carriers may have decreased ovarian reserve compared with women without BRCA mutations, as well as an earlier natural menopause (33).…”
Section: Aim Of the Studysupporting
confidence: 72%
“…The increase in levels of IGF-I and insulin during puberty may be related to the increased prevalence of PCOS in adolescence. 14 The prevalences showed by population studies range from about 5% to 10% of women of reproductive age, 15 a range which encompasses the 6.2% found in this study. Bridges et al, 16 when analyzing the growth of the ovaries and the prevalence of polycystic ovary in 358 girls in a pediatric endocrinology outpatient clinic of a hospital in the city of Middletown, in the United States, found a 6% prevalence of PCOS at 6 years of age and 26% at 15 years of age.…”
Section: Discussionsupporting
confidence: 56%
“…O câncer de mama também é um importante tópico quando se abordam as neoplasias mais comuns em mulheres, na realidade é o tipo de câncer mais diagnosticado de todos os carcinomas. Entretanto a relação entre SOP e o Ca de mama ainda carece de estudos e uma investigação mais aprofundada (Spritzer et al 2005).…”
Section: Yin Et Al (unclassified